Anti-pulling high-toughness capacitor film and preparation method thereof

Through a specific raw material combination and preparation process, the high -tough capacitor film is prepared to solve the lack of existing thin film in terms of pull -up, toughness and heat resistance, and achieve good mechanics and heat resistance, suitable for promotion.

CN119331359AInactive Publication Date: 2025-01-21HENAN HUAJIA NEW MATERIAL TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411448936.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing capacitor films have shortcomings in terms of pull resistance, toughness and heat resistance, and further improvement is needed.

Method used

Use specific raw material combinations and preparation processes, including clustering 4-methyl-1-pentinyne, and other regulatory polypropylene, peroxidine, paraffin oil, 4-acryl oxygenyl-2-hydroxyl diodes, triape ​​three Pyramia glycatocyanate, hydroxide, functional auxiliary, coordinator, antioxidant and styrene-ethylene-borne-lyeylene embedded section, through squeezing, stretching, cooling, and Steps and other steps are prepared to pull high tough capacitor film.

Benefits of technology

The better mechanical properties and excellent thermal resistance of capacitor film are realized, and it effectively guarantees its quality and quality and has a broader market prospect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005088498690000111
    Figure BDA0005088498690000111
  • Figure BDA0005088498690000121
    Figure BDA0005088498690000121
Patent Text Reader

Abstract

The invention relates to the technical field of capacitor film production, in particular to an anti-pulling high-toughness capacitor film and a preparation method thereof. The anti-pulling high-toughness capacitor film is prepared from the following raw materials in parts by weight: 30 to 40 parts of poly (4-methyl-1-pentene), 10 to 20 parts of isotatic polypropylene, 3 to 5 parts of dicumyl peroxide, 5 to 7 parts of paraffin oil, 5 to 8 parts of 4-allyloxy-2-hydroxybenzophenone, 3 to 5 parts of triallyl isocyanurate, 3 to 5 parts of cerium hydroxide, 5 to 10 parts of functional additive, 7 to 12 parts of synergistic additive, 2 to 5 parts of antioxidant and 8 parts of antioxidant. 12 parts of a styrene-ethylene-butylene-styrene block copolymer; the anti-pulling high-toughness capacitor film prepared by the invention not only has better mechanical properties, but also has excellent heat resistance, so that the quality of the capacitor film is effectively ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of capacitor film production, in particular to a tensile-resistant high-toughness capacitor film and a preparation method thereof. Background Art

[0002] Film capacitors are excellent capacitors because of their many excellent properties. Its main characteristics are as follows: non-polarity, high insulation impedance, excellent frequency characteristics (wide frequency response), and low dielectric loss; and the capacitor film is an important component of the capacitor.

[0003] In the patent document with application number "CN202210212776.4" and titled "A capacitor film material and its preparation method", a capacitor film material is disclosed, and its raw materials include: polypropylene, maleic anhydride grafted polystyrene and polystyrene modified composite nanofiller, wherein the weight of the polystyrene modified composite nanofiller is 1-2wt% of the total weight of polypropylene and maleic anhydride grafted polystyrene; in the preparation process of the polystyrene modified composite nanofiller, nano-ceramic particles, hexagonal boron nitride nanosheets, and surfactants are uniformly dispersed in water, and then styrene and initiator are added to react to obtain polystyrene modified composite nanofiller. The present invention also discloses a method for preparing the above capacitor film material. The present invention has good dielectric properties and breakdown properties, and has good mechanical properties.

[0004] Although the film material manufactured by the above patent document has certain advantages such as excellent mechanical properties, its own tensile strength, toughness and heat resistance are relatively insufficient and still need to be further improved. Based on this, the present invention provides a tensile-resistant and high-toughness capacitor film and a preparation method thereof to solve the above technical problems. Summary of the invention

[0005] The purpose of the present invention is to provide a tear-resistant and high-toughness capacitor film and a preparation method thereof. The prepared tear-resistant and high-toughness capacitor film not only has good mechanical properties, but also has excellent heat resistance, effectively ensuring its quality.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] The first aspect of the present invention provides a tear-resistant and high-toughness capacitor film, which is composed of the following raw materials in parts by weight: 30 to 40 parts of poly-4-methyl-1-pentene, 10 to 20 parts of isotactic polypropylene, 3 to 5 parts of diisopropylbenzene peroxide, 5 to 7 parts of paraffin oil, 5 to 8 parts of 4-propyleneoxy-2-hydroxybenzophenone, 3 to 5 parts of triallyl isocyanurate, 3 to 5 parts of cerium hydroxide, 5 to 10 parts of functional additives, 7 to 12 parts of synergistic additives, 2 to 5 parts of antioxidants and 8 to 12 parts of styrene-ethylene-butylene-styrene block copolymers.

[0008] The present invention is further configured as follows: the preparation process of the functional additive is as follows:

[0009] The composite base material is added into a sodium hydroxide aqueous solution with a mass concentration of 2.8 to 3.6% at a dosage ratio of 0.05 to 0.15 g / mL, and ultrasonically treated at 42 to 46° C. for 20 to 30 minutes, washed with deionized water for 2 to 4 times, and then vacuum-freeze-dried for 15 to 25 hours to obtain a pretreated product;

[0010] The pretreated product is added into the hydrolyzate at a dosage ratio of 0.02-0.06 g / mL, and treated for 150-170 min at 48-52° C. and 210-230 r / min, and then carbon nanotubes are added thereto, the temperature is raised to 64-66° C., and the treatment is continued for 300-340 min. After filtration, the filter cake is washed with deionized water for 2-4 times, and dried at 65-70° C. for 22-24 hours to obtain a functional additive.

[0011] The present invention is further configured as follows: the composite base material is formed by mixing coconut petiole fiber and poplar bark fiber in a mass ratio of 1:0.2-0.4.

[0012] The present invention is further configured as follows: the preparation process of the hydrolyzate is as follows:

[0013] Mix γ-aminopropyltriethoxysilane and 90% ethanol solution in a mass ratio of 1:10-15;

[0014] Add glacial acetic acid to the obtained mixed solution to adjust the pH to 5.0-5.6, and stir for 60-80 minutes at 24-26° C. and 80-120 r / min to obtain a hydrolyzate.

[0015] The present invention is further configured as follows: the added amount of the carbon nanotubes is 6.5-7.5% of the mass of the pretreated material.

[0016] The present invention is further configured as follows: the preparation process of the synergistic aid is as follows:

[0017] Tetrabutyl titanate and anhydrous ethanol are mixed at a volume ratio of 5 to 6:1 at 80 to 140 r / min for 30 to 40 minutes, and then glacial acetic acid in an amount of 8.5% by volume of tetrabutyl titanate is added thereto, and stirring is continued for 20 to 30 minutes;

[0018] Then, 12-14% diatomaceous earth of tetra-n-butyl titanate mass is added thereto, stirred at 550-650 r / min for 60-70 min, and then centrifuged. The centrifuged product is washed 2-4 times with deionized water, and dried in a vacuum oven at 60-70° C. for 24-28 h.

[0019] The obtained dry product was ground and then calcined at 420-450° C. for 120 min to obtain a synergistic aid.

[0020] The present invention is further configured as follows: the centrifugal speed is set to 6000-9000 r / min, and the time is 15-20 min.

[0021] The present invention is further configured as follows: the antioxidant is selected from any one of antioxidant 1010, antioxidant 1076, and antioxidant CA.

[0022] The second aspect of the present invention: also provides a method for preparing the above-mentioned tensile-resistant high-toughness capacitor film, comprising the following steps:

[0023] Step 1, accurately weigh poly-4-methyl-1-pentene, isotactic polypropylene, diisopropylbenzene peroxide, paraffin oil, 4-propyleneoxy-2-hydroxybenzophenone, triallyl isocyanurate, cerium hydroxide, functional additives, synergistic additives, antioxidants and styrene-ethylene-butylene-styrene block copolymer for later use;

[0024] Step 2, stirring and mixing poly-4-methyl-1-pentene and paraffin oil to obtain film material A;

[0025] Step 3, stirring and mixing isotactic polypropylene and 4-propyleneoxy-2-hydroxybenzophenone to obtain film material B;

[0026] Step 4: uniformly mix film material A, film material B, diisopropylbenzene peroxide, triallyl isocyanurate, cerium hydroxide, functional additives, synergistic additives, antioxidants and styrene-ethylene-butylene-styrene block copolymer at 80-100 r / min, then heat to 380-420° C., and then keep warm for 60-70 minutes. After the reaction is completed, the temperature is reduced to 75° C., and then the material is discharged, cooled and pelletized to obtain a mixture;

[0027] Step 5: Extruding the mixture through the gap of the flat die of the extruder, stretching it with a stretching roller, cooling it with a cooling roller, and then annealing it to obtain a tear-resistant and high-toughness capacitor film.

[0028] The present invention is further configured as follows: in step five, the extrusion temperature of the flat die slit of the extruder is 255-260° C., the stretching ratio of the stretching roller is 1:90-110 times, the annealing temperature is 104-108° C., and the annealing time is 40-90 min.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] The present invention uses poly-4-methyl-1-pentene, isotactic polypropylene, dicumyl peroxide, paraffin oil, 5 parts of 4-propyleneoxy-2-hydroxybenzophenone, triallyl isocyanurate, cerium hydroxide, functional additives, synergistic additives, antioxidants and styrene-ethylene-butylene-styrene block copolymer as raw materials, and obtains film material A by stirring and mixing poly-4-methyl-1-pentene and paraffin oil. Isotactic polypropylene and 4-propyleneoxy-2-hydroxybenzophenone are stirred and mixed to obtain film material B. Then, film material A, film material B, dicumyl peroxide, triallyl isocyanurate, cerium hydroxide, functional additives, synergistic additives, antioxidants and styrene-ethylene-butylene-styrene block copolymer are mixed uniformly, and then the mixture is heated, kept warm for reaction, discharged, cooled and pelletized to obtain a mixture, which is extruded through the gap of a flat die of an extruder, stretched by a stretching roller, cooled by a cooling roller, and then annealed to obtain a tensile-resistant high-toughness capacitor film. The tear-resistant high-toughness capacitor film prepared by the present invention not only has good mechanical properties, but also has excellent heat resistance, effectively ensuring its quality. The tear-resistant high-toughness capacitor film and the preparation method thereof provided by the present invention have a broader market prospect and are more suitable for promotion. DETAILED DESCRIPTION

[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] Example 1

[0033] The present embodiment provides a tensile-resistant and high-toughness capacitor film, which is composed of the following raw materials in parts by weight: 30 parts of poly-4-methyl-1-pentene, 10 parts of isotactic polypropylene, 3 parts of diisopropyl peroxide, 5 parts of paraffin oil, 5 parts of 4-propyleneoxy-2-hydroxybenzophenone, 3 parts of triallyl isocyanurate, 3 parts of cerium hydroxide, 5 parts of functional additives, 7 parts of synergistic additives, 2 parts of antioxidants and 8 parts of styrene-ethylene-butylene-styrene block copolymer.

[0034] The preparation process of the functional additive is as follows:

[0035] The composite base material was added into a sodium hydroxide aqueous solution with a mass concentration of 2.8% at a dosage ratio of 0.05 g / mL, and ultrasonically treated at 42° C. for 20 min, washed twice with deionized water, and then vacuum-freeze-dried for 15 h to obtain a pretreated product;

[0036] The pretreated product was added into the hydrolyzate at a dosage ratio of 0.02 g / mL, treated at 48°C and 210 r / min for 150 min, and then carbon nanotubes were added thereto. The temperature was raised to 64°C and the treatment was continued for 300 min. After filtration, the filter cake was washed with deionized water for 2 hours and dried at 65°C for 22 hours to obtain a functional additive.

[0037] Furthermore, the composite base material is formed by mixing coconut petiole fiber and poplar bark fiber in a mass ratio of 1:0.2.

[0038] The preparation process of the hydrolyzate is as follows:

[0039] Mix γ-aminopropyltriethoxysilane and 90% ethanol solution in a mass ratio of 1:10;

[0040] Then, glacial acetic acid was added to the obtained mixed solution to adjust the pH to 5.0, and the mixture was stirred at 24° C. and 80 r / min for 60 min to obtain a hydrolyzate.

[0041] The added amount of carbon nanotubes was 6.5% of the pretreated material.

[0042] In addition, the preparation process of the synergist is as follows:

[0043] Tetrabutyl titanate and anhydrous ethanol were mixed at a volume ratio of 5:1 at 80 r / min for 30 min, and then glacial acetic acid (8.5% by volume of tetrabutyl titanate) was added thereto, and stirring was continued for 20 min;

[0044] Then, 12% diatomaceous earth by weight of tetra-n-butyl titanate was added thereto, stirred at 550 r / min for 60 min, and then centrifuged. The centrifuged product was washed twice with deionized water and dried in a vacuum oven at 60° C. for 24 h.

[0045] The obtained dry product was ground and calcined at 420°C for 120 min to obtain a synergistic aid.

[0046] Furthermore, the centrifugal speed was set to 6000 r / min and the time was 15 min.

[0047] In this embodiment, it should be noted that the diatomite was purchased from Lingshou County Qihong Mining Co., Ltd.

[0048] Among them, antioxidant 1010 is selected as the antioxidant.

[0049] In addition, this embodiment also provides a method for preparing the above-mentioned tensile-resistant high-toughness capacitor film, comprising the following steps:

[0050] Step 1, accurately weigh poly-4-methyl-1-pentene, isotactic polypropylene, diisopropylbenzene peroxide, paraffin oil, 4-propyleneoxy-2-hydroxybenzophenone, triallyl isocyanurate, cerium hydroxide, functional additives, synergistic additives, antioxidants and styrene-ethylene-butylene-styrene block copolymer for later use;

[0051] Step 2, stirring and mixing poly-4-methyl-1-pentene and paraffin oil to obtain film material A;

[0052] Step 3, stirring and mixing isotactic polypropylene and 4-propyleneoxy-2-hydroxybenzophenone to obtain film material B;

[0053] Step 4: uniformly mix film material A, film material B, diisopropylbenzene peroxide, triallyl isocyanurate, cerium hydroxide, functional additives, synergistic additives, antioxidants and styrene-ethylene-butylene-styrene block copolymer at 80 r / min, then heat to 380° C., and then keep warm for 60 minutes. After the reaction is completed, the temperature is reduced to 75° C., and then the material is discharged, cooled and pelletized to obtain a mixture;

[0054] Step 5: Extruding the mixture through the gap of the flat die of the extruder, stretching it with a stretching roller, cooling it with a cooling roller, and then annealing it to obtain a tear-resistant and high-toughness capacitor film.

[0055] Among them, the extrusion temperature of the flat die of the extruder is 255°C, the stretching ratio of the stretching roller is 1:90 times, the annealing temperature is 104°C, and the annealing time is 40 minutes.

[0056] Example 2

[0057] The preparation method of the tear-resistant high-toughness capacitor film provided in this embodiment is basically the same as that in Embodiment 1, except that: the specific raw material composition and the specific preparation method of the tear-resistant high-toughness capacitor film in this embodiment are different; the specific raw material composition and the specific preparation method of the tear-resistant high-toughness capacitor film in this embodiment are as follows:

[0058] A tensile-resistant high-toughness capacitor film is composed of the following raw materials in parts by weight: 35 parts of poly-4-methyl-1-pentene, 15 parts of isotactic polypropylene, 4 parts of dicumyl peroxide, 6 parts of paraffin oil, 6 parts of 4-propyleneoxy-2-hydroxybenzophenone, 4 parts of triallyl isocyanurate, 4 parts of cerium hydroxide, 7 parts of functional additives, 10 parts of synergistic additives, 3 parts of antioxidants and 10 parts of styrene-ethylene-butylene-styrene block copolymer.

[0059] The preparation process of the functional additive is as follows:

[0060] The composite base material is added into a sodium hydroxide aqueous solution with a mass concentration of 2.8 to 3.6% at a dosage ratio of 0.05 to 0.15 g / mL, and ultrasonically treated at 42 to 46° C. for 20 to 30 minutes, washed with deionized water for 2 to 4 times, and then vacuum-freeze-dried for 15 to 25 hours to obtain a pretreated product;

[0061] The pretreated product was added into the hydrolyzate at a dosage ratio of 0.04 g / mL, treated at 50°C and 220 r / min for 160 min, and then carbon nanotubes were added thereto. The temperature was raised to 65°C and the treatment was continued for 320 min. After filtration, the filter cake was washed with deionized water for 3 hours and dried at 67°C for 23 hours to obtain a functional additive.

[0062] Furthermore, the composite base material is formed by mixing coconut petiole fiber and poplar bark fiber in a mass ratio of 1:0.3.

[0063] The preparation process of the hydrolyzate is as follows:

[0064] Mix γ-aminopropyltriethoxysilane and 90% ethanol solution in a mass ratio of 1:12;

[0065] Then, glacial acetic acid was added to the obtained mixed solution to adjust the pH to 5.3, and the mixture was stirred at 25° C. and 100 r / min for 70 min to obtain a hydrolyzate.

[0066] The amount of carbon nanotubes added was 7% of the pretreated material.

[0067] In addition, the preparation process of the synergist is as follows:

[0068] Tetrabutyl titanate and anhydrous ethanol were mixed at a volume ratio of 6:1 at 110 r / min for 35 min, and then glacial acetic acid (8.5% by volume of tetrabutyl titanate) was added thereto, and stirring was continued for 25 min;

[0069] Then, 13% diatomaceous earth by weight of tetra-n-butyl titanate was added thereto, stirred at 600 r / min for 65 min, and then centrifuged. The centrifuged product was washed three times with deionized water and dried in a vacuum oven at 65° C. for 26 h.

[0070] The obtained dry product was ground and calcined at 435°C for 120 min to obtain a synergistic aid.

[0071] Furthermore, the centrifugal speed was set to 7500 r / min and the time was 17 min.

[0072] In this embodiment, it should be noted that the diatomite was purchased from Lingshou County Qihong Mining Co., Ltd.

[0073] Among them, antioxidant 1076 is selected as the antioxidant.

[0074] In addition, this embodiment also provides a method for preparing the above-mentioned tensile-resistant high-toughness capacitor film, comprising the following steps:

[0075] Step 1, accurately weigh poly-4-methyl-1-pentene, isotactic polypropylene, diisopropylbenzene peroxide, paraffin oil, 4-propyleneoxy-2-hydroxybenzophenone, triallyl isocyanurate, cerium hydroxide, functional additives, synergistic additives, antioxidants and styrene-ethylene-butylene-styrene block copolymer for later use;

[0076] Step 2, stirring and mixing poly-4-methyl-1-pentene and paraffin oil to obtain film material A;

[0077] Step 3, stirring and mixing isotactic polypropylene and 4-propyleneoxy-2-hydroxybenzophenone to obtain film material B;

[0078] Step 4: uniformly mix film material A, film material B, diisopropylbenzene peroxide, triallyl isocyanurate, cerium hydroxide, functional additives, synergistic additives, antioxidants and styrene-ethylene-butylene-styrene block copolymer at 90 r / min, then heat to 400° C., and then keep warm for 65 minutes. After the reaction is completed, the temperature is reduced to 75° C., and then the material is discharged, cooled and pelletized to obtain a mixture;

[0079] Step 5: Extruding the mixture through the gap of the flat die of the extruder, stretching it with a stretching roller, cooling it with a cooling roller, and then annealing it to obtain a tear-resistant and high-toughness capacitor film.

[0080] Among them, the extrusion temperature of the flat die of the extruder is 257°C, the stretching ratio of the stretching roller is 1:100 times, the annealing temperature is 106°C, and the annealing time is 65min.

[0081] Example 3

[0082] The preparation method of the tear-resistant high-toughness capacitor film provided in this embodiment is basically the same as that in Embodiment 1, except that: the specific raw material composition and the specific preparation method of the tear-resistant high-toughness capacitor film in this embodiment are different; the specific raw material composition and the specific preparation method of the tear-resistant high-toughness capacitor film in this embodiment are as follows:

[0083] A tensile-resistant high-toughness capacitor film is composed of the following raw materials in parts by weight: 40 parts of poly-4-methyl-1-pentene, 20 parts of isotactic polypropylene, 5 parts of dicumyl peroxide, 7 parts of paraffin oil, 8 parts of 4-propyleneoxy-2-hydroxybenzophenone, 5 parts of triallyl isocyanurate, 5 parts of cerium hydroxide, 10 parts of functional additives, 12 parts of synergistic additives, 5 parts of antioxidants and 12 parts of styrene-ethylene-butylene-styrene block copolymer.

[0084] The preparation process of the functional additive is as follows:

[0085] The composite base material was added into a sodium hydroxide aqueous solution with a mass concentration of 3.6% at a dosage ratio of 0.15 g / mL, and ultrasonically treated at 46° C. for 30 min, washed with deionized water for 4 times, and then vacuum-freeze-dried for 25 h to obtain a pretreated product;

[0086] The pretreated material was added into the hydrolyzate at a dosage ratio of 0.06 g / mL, and treated at 52°C and 230 r / min for 170 min. Then, carbon nanotubes were added thereto, the temperature was raised to 66°C, and the treatment was continued for 340 min. After filtration, the filter cake was washed with deionized water for 4, and dried at 70°C for 24 h to obtain a functional additive.

[0087] Furthermore, the composite base material is formed by mixing coconut petiole fiber and poplar bark fiber in a mass ratio of 1:0.4.

[0088] The preparation process of the hydrolyzate is as follows:

[0089] Mix γ-aminopropyltriethoxysilane and 90% ethanol solution in a mass ratio of 1:15;

[0090] Then, glacial acetic acid was added to the obtained mixed solution to adjust the pH to 5.6, and the mixture was stirred at 26° C. and 120 r / min for 80 min to obtain a hydrolyzate.

[0091] The added amount of carbon nanotubes was 7.5% of the pretreated material.

[0092] In addition, the preparation process of the synergist is as follows:

[0093] Tetrabutyl titanate and anhydrous ethanol were mixed at a volume ratio of 6:1 at 140 r / min for 30 to 40 minutes, and then glacial acetic acid (8.5% by volume of tetrabutyl titanate) was added thereto, and stirring was continued for 30 minutes;

[0094] Then, 14% diatomaceous earth by weight of tetra-n-butyl titanate was added thereto, stirred at 650 r / min for 70 min, and then centrifuged. The centrifuged product was washed 4 times with deionized water and dried in a vacuum oven at 70°C for 28 h.

[0095] The obtained dry product was ground and calcined at 450°C for 120 min to obtain a synergistic aid.

[0096] Furthermore, the centrifugal speed was set to 9000 r / min and the time was 20 min.

[0097] In this embodiment, it should be noted that the diatomite was purchased from Lingshou County Qihong Mining Co., Ltd.

[0098] Among them, the antioxidant is antioxidant CA.

[0099] In addition, this embodiment also provides a method for preparing the above-mentioned tensile-resistant high-toughness capacitor film, comprising the following steps:

[0100] Step 1, accurately weigh poly-4-methyl-1-pentene, isotactic polypropylene, diisopropylbenzene peroxide, paraffin oil, 4-propyleneoxy-2-hydroxybenzophenone, triallyl isocyanurate, cerium hydroxide, functional additives, synergistic additives, antioxidants and styrene-ethylene-butylene-styrene block copolymer for later use;

[0101] Step 2, stirring and mixing poly-4-methyl-1-pentene and paraffin oil to obtain film material A;

[0102] Step 3, stirring and mixing isotactic polypropylene and 4-propyleneoxy-2-hydroxybenzophenone to obtain film material B;

[0103] Step 4: uniformly mix film material A, film material B, diisopropylbenzene peroxide, triallyl isocyanurate, cerium hydroxide, functional additives, synergistic additives, antioxidants and styrene-ethylene-butylene-styrene block copolymer at 100 r / min, then heat to 420° C., and then keep warm for 60 to 70 minutes. After the reaction is completed, the temperature is reduced to 75° C., and then the material is discharged, cooled and pelletized to obtain a mixture;

[0104] Step 5: Extruding the mixture through the gap of the flat die of the extruder, stretching it with a stretching roller, cooling it with a cooling roller, and then annealing it to obtain a tear-resistant and high-toughness capacitor film.

[0105] Among them, the extrusion temperature of the flat die of the extruder is 260°C, the stretching ratio of the stretching roller is 1:110 times, the annealing temperature is 108°C, and the annealing time is 90min.

[0106] Comparative Example 1: The difference from Example 1 is that this example does not contain a functional additive.

[0107] Comparative Example 2: The difference from Example 1 is that this example does not contain a synergistic aid.

[0108] Comparative Example 3: The difference from Example 1 is that this example does not contain cerium hydroxide.

[0109] Performance test: The tear-resistant high-toughness capacitor film samples provided by Examples 1 to 3 and Comparative Examples 1 to 3 are marked as Examples 1 to 3 and Comparative Examples 1 to 3, respectively; and the relevant properties of the tear-resistant high-toughness capacitor films provided by Examples 1 to 3 and Comparative Examples 1 to 3 are tested as follows:

[0110] 1. Tensile strength and elongation at break test: The test method is ISO527-1:2012&ISO527-3:1995 / Cor.2:2001, the sample width is 25mm, the sample thickness is 0.196mm, the test speed is 500mm / min, the chuck distance is 50mm, the test environment temperature is 23±2℃, and the test environment humidity is 50±5%RH.

[0111] 2. Heat resistance test: Make the sample into a specimen with a size of 120mm×10mm×4mm, place it at a humidity of (45±5)% and a temperature of 180℃ for 1000h, and observe the state of the sample.

[0112] The obtained test data are recorded in Table 1 and Table 2 below:

[0113] Table 1 Mechanical properties test results of each group of capacitor films

[0114] Group Tensile strength / MPa Elongation at break / % Example 1 Group 215 60 Example 2 Group 212 58 Example 3 Group 213 58 Comparison group 1 175 36 Comparison of 2 groups 185 40 Comparison of 3 groups 190 42

[0115] Table 2 Test results of heat resistance of capacitor films of each group

[0116]

[0117]

[0118] By comparing and analyzing the relevant data in Table 1 and Table 2, it can be seen that the tear-resistant high-toughness capacitor film prepared by the present invention not only has good mechanical properties, but also has excellent heat resistance, effectively ensuring its quality. This shows that the tear-resistant high-toughness capacitor film and the preparation method thereof provided by the present invention have a broader market prospect and are more suitable for promotion.

[0119] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0120] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A tensile-resistant and high-toughness capacitor film, characterized in that: The invention is composed of the following raw materials in parts by weight: 30 to 40 parts of poly-4-methyl-1-pentene, 10 to 20 parts of isotactic polypropylene, 3 to 5 parts of dicumyl peroxide, 5 to 7 parts of paraffin oil, 5 to 8 parts of 4-propyleneoxy-2-hydroxybenzophenone, 3 to 5 parts of triallyl isocyanurate, 3 to 5 parts of cerium hydroxide, 5 to 10 parts of functional additives, 7 to 12 parts of synergistic additives, 2 to 5 parts of antioxidants and 8 to 12 parts of styrene-ethylene-butylene-styrene block copolymer.

2. The tear-resistant and high-toughness capacitor film according to claim 1, characterized in that: The preparation process of the functional additive is as follows: The composite base material is added into a sodium hydroxide aqueous solution with a mass concentration of 2.8 to 3.6% at a dosage ratio of 0.05 to 0.15 g / mL, and ultrasonically treated at 42 to 46° C. for 20 to 30 minutes, washed with deionized water for 2 to 4 times, and then vacuum-freeze-dried for 15 to 25 hours to obtain a pretreated product; The pretreated product is added into the hydrolyzate at a dosage ratio of 0.02-0.06 g / mL, and treated for 150-170 min at 48-52° C. and 210-230 r / min, and then carbon nanotubes are added thereto, the temperature is raised to 64-66° C., and the treatment is continued for 300-340 min. After filtration, the filter cake is washed with deionized water for 2-4 times, and dried at 65-70° C. for 22-24 hours to obtain a functional additive.

3. The tear-resistant and high-toughness capacitor film according to claim 2, characterized in that: The composite base material is prepared by mixing coconut petiole fiber and poplar bark fiber in a mass ratio of 1:0.2-0.

4.

4. The tear-resistant and high-toughness capacitor film according to claim 2, characterized in that: The preparation process of the hydrolyzate is as follows: Mix γ-aminopropyltriethoxysilane and 90% ethanol solution in a mass ratio of 1:10-15; Add glacial acetic acid to the obtained mixed solution to adjust the pH to 5.0-5.6, and stir for 60-80 minutes at 24-26° C. and 80-120 r / min to obtain a hydrolyzate.

5. The tear-resistant and high-toughness capacitor film according to claim 2, characterized in that: The added amount of the carbon nanotubes is 6.5-7.5% of the mass of the pretreated material.

6. The tear-resistant and high-toughness capacitor film according to claim 1, characterized in that: The preparation process of the synergistic aid is as follows: Tetrabutyl titanate and anhydrous ethanol are mixed at a volume ratio of 5 to 6:1 at 80 to 140 r / min for 30 to 40 minutes, and then glacial acetic acid in an amount of 8.5% by volume of tetrabutyl titanate is added thereto, and stirring is continued for 20 to 30 minutes; Then, 12-14% diatomaceous earth of tetra-n-butyl titanate mass is added thereto, stirred at 550-650 r / min for 60-70 min, and then centrifuged. The centrifuged product is washed 2-4 times with deionized water, and dried in a vacuum oven at 60-70° C. for 24-28 h. The obtained dry product was ground and then calcined at 420-450° C. for 120 min to obtain a synergistic aid.

7. The tear-resistant and high-toughness capacitor film according to claim 6, characterized in that: The centrifugal speed is set to 6000-9000 r / min, and the time is 15-20 min.

8. The tear-resistant and high-toughness capacitor film according to claim 1, characterized in that: The antioxidant is selected from any one of antioxidant 1010, antioxidant 1076, and antioxidant CA.

9. The method for preparing a tear-resistant and high-toughness capacitor film according to any one of claims 1 to 8, characterized in that: The following steps are involved: Step 1, accurately weigh poly-4-methyl-1-pentene, isotactic polypropylene, diisopropylbenzene peroxide, paraffin oil, 4-propyleneoxy-2-hydroxybenzophenone, triallyl isocyanurate, cerium hydroxide, functional additives, synergistic additives, antioxidants and styrene-ethylene-butylene-styrene block copolymer for later use; Step 2, stirring and mixing poly-4-methyl-1-pentene and paraffin oil to obtain film material A; Step 3, stirring and mixing isotactic polypropylene and 4-propyleneoxy-2-hydroxybenzophenone to obtain film material B; Step 4: uniformly mix film material A, film material B, diisopropylbenzene peroxide, triallyl isocyanurate, cerium hydroxide, functional additives, synergistic additives, antioxidants and styrene-ethylene-butylene-styrene block copolymer at 80-100 r / min, then heat to 380-420° C., and then keep warm for 60-70 minutes. After the reaction is completed, the temperature is reduced to 75° C., and then the material is discharged, cooled and pelletized to obtain a mixture; Step 5: Extruding the mixture through the gap of the flat die of the extruder, stretching it with a stretching roller, cooling it with a cooling roller, and then annealing it to obtain a tear-resistant and high-toughness capacitor film.

10. The method for preparing a tear-resistant and high-toughness capacitor film according to claim 9, characterized in that: In the step five, the extrusion temperature of the flat die slit of the extruder is 255-260° C., the stretching ratio of the stretching roller is 1:90-110 times, the annealing temperature is 104-108° C., and the annealing time is 40-90 min.

Citation Information

Patent Citations

  • A thin film material for capacitors and its preparation method

    CN114479280B

  • Metalized film with excellent overall performance for capacitor and preparation method thereof

    CN103937098A

  • Biaxially oriented poly (4-methyl-1-pentene) film and preparation method thereof

    CN112406146A

  • Polypropylene-high-temperature-resistant polymer blended film, preparation method thereof and capacitor core

    CN115260647A

  • Preparation method of film for photovoltaic capacitor

    CN118702951A